Topos, Typos, Tekton. L'appropriata collocazione delle cose / Topos, Typos, Tekton. The appropriate placement of things - Mirko Russo (Festival dell'Architettura Magazine, 2017)
Il testo indaga le relazioni tra procedure compositive e modalità costruttive, in particolare ambisce a ribadire il potenziale espressivo della costruzione, riaffermando la tettonica come principio interno all’architettura stessa, in antitesi alla tendenza contemporanea di derivare la legittimità dell’opera da discorsi estranei ad essa. / The text explores the relationship between the project composition and the construction methods, above all aims to emphasize the expressive potential of construction, meaning the "tectonics" as an internal architectural principle in opposition to the contemporary trend to deduce the validity of the architecture from what it is different.